Evaluation of the Exposure-Response Relationship of Lung Cancer Mortality and Occupational Exposure to Hexavalent Chromium Based on Published Epidemiological Data - Edwin van Wijngaarden; Kenneth A. Mundt; Rose S. Luippold (SAGE Publishing, 2004)
Some have suggested a threshold mechanism for the carcinogenicity of exposure to hexavalent chromium, Cr(VI). We evaluated the nature of the exposure-response relationship between occupational exposure to Cr(VI) and respiratory cancer based on results of two recently published epidemiological cohort studies. The combined cohort comprised a total of 2,849 workers employed at two U.S. chromate production plants between 1940 and 1974. Standardized mortality ratios (SMRs) for lung cancer in relation to cumulative Cr(VI) exposure categories were reported using regional mortality rates. Linear additive and multiplicative relative risk regression models were fit to the SMRs of the individual and combined studies. Both models fit the data from the individual studies reasonably well; however, the fit was somewhat less adequate for the pooled data. Meta-analysis of the slope estimates obtained from the multiplicative relative risk model showed substantial heterogeneity between the two epidemiological studies. In conclusion, these data indicate that a linear dose response describes the relationship between Cr(VI) and lung cancer reasonably well, and therefore these analyses do not necessarily support the threshold hypothesis for the lung carcinogenicity of Cr(VI). However, these results must be interpreted with recognition of the limitations of the use of epidemiological data in the evaluation of nonlinear exposure-response patterns.